Performance of Chickpea Varieties on Growth and Yield through Water Absorbents under Late Sown Condition - Yadav, Pradeep; Singh, Amit Kumar; Maurya, Shravan Kumar; Yadav, Akhilesh Chandra; Yadav, Rajat Kumar (International Journal of Economic Plants, 2023)
This study was carried out in the winter of 2020–21 at College Research Farm Banda University of Agriculture and Technology, Banda UP, India. Experiment was conducted in split plot design with two factor-treatments and three replications with a holistic aim to search out the best variety and water absorbent that enhance the crop yield and mitigate the moisture deficit stress. The treatments consisted of main plot: three water absorbents viz., Hydrogel @ 5.0 kg ha- 1, two foliar application of Salicylic acid @ 150 ppm, Hydrogel @ 5.0 kg ha-1 followed by two foliar application of Salicylic acid @ 150 ppm and sub-plot: five varieties viz., JG-14, JG-16, JG-18, JG-36 and RVG-202. The conducted field study during rabi 2020-21 reveals that Chickpea variety “JG- 18” when sown on November 9th at a spacing of 30×10 cm2 apart and fertilized at 25:60:30 kg of N:P:K ha-1 under rainfed late sown condition was performed significantly superior over other varieties irrespective of water-absorbents applied. The mixed application of water- absorbents as basal (hydrogel @ 5 kg ha-1) and foliar (salicylic acid @ 150 ppm ha-1 twice at flower initiation and pod formation) proved remarkable in terms of growth that maximized yield. Among the treatment combination studies, the RVG-202 with the basal application of hydrogel @ 5 kg ha-1 and two foliar sprays of Salicylic acid @ 150 ppm at flowering initiation and pod formation significantly produced more number of root nodules at 45 and 60 DAS, took more number of days to mature and out-yielded the crop productivity.